Poly(dopamine) surface‐modified polyethylene separator with electrolyte‐philic characteristics for enhancing the performance of sodium‐ion batteries. (26th November 2021) - Ho, Van‐Chuong; Nguyen, Bao Tran Duy; Thi, Hai Yen Nguyen; Kim, Jeong F; Mun, Junyoung
Summary: Sodium‐ion batteries (NIBs) are promising candidates for next‐generation rechargeable batteries with high energy density. Na ion with global abundance exhibits similar chemical characteristics to Li ion for rechargeable batteries. However, the polyethylene (PE) membrane, a conventional safety separator used for lithium‐ion batteries, is inappropriate for NIBs due to its hydrophobic properties in NIBs liquid electrolytes and extremely poor ionic conductivity. Therefore, modifications to the PE separator are required to induce better electrochemical performance NIBs. Herein, we introduce a poly(dopamine)‐modified PE separator by a simple dip‐coating method, whereby the incorporation of the dopamine layer renders the membrane more hydrophilic in the liquid electrolyte of the NIBs. The PDA‐PE separator exhibits high ionic conductivity and a long cycle life, and is stable with different current rates for Na||Na symmetric cells. Also, Na half‐cell systems, consisting of hard carbon and Na metal electrodes, demonstrate considerably improved cyclability and high reversible discharge/charge with cells using PDA‐treated PE separators.